2004
DOI: 10.14742/ajet.1361
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of blogs as learning spaces in the higher education sector

Abstract: <span>'Blogging' - a contraction of the term 'web logging' - is perhaps best described as a form of micro-publishing. Easy to use, from any Internet connection point, blogging has become firmly established as a web based communications tool. The blogging phenomenon has evolved from its early origin as a medium for the publication of simple, online personal diaries, to the latest disruptive technology, the 'killer app' that has the capacity to engage people in collaborative activity, knowledge sharing, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
336
0
25

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(392 citation statements)
references
References 2 publications
9
336
0
25
Order By: Relevance
“…The term 'blog' is a contraction of 'Web log', and is thought to have come into use in 1999 (Williams and Jacobs, 2004). The blog in its most basic form is an online journal with entries displayed in reverse chronological order.…”
Section: Blogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term 'blog' is a contraction of 'Web log', and is thought to have come into use in 1999 (Williams and Jacobs, 2004). The blog in its most basic form is an online journal with entries displayed in reverse chronological order.…”
Section: Blogsmentioning
confidence: 99%
“…As an educational tool, therefore, Blogs provide a means of sharing knowledge and a forum for debate on any conceivable topic. In Williams and Jacobs' (2004) study of an MBA blog at Brisbane Graduate School of Business, most students felt that the blog 'increased the level of meaningful intellectual exchange' amongst peers. Glogoff (2005) sees the addition of comments to blog entries as a useful means of giving immediate feedback to students on their blog entries, which in turn can be an aid to directed learning and guided discovery.…”
Section: Blogsmentioning
confidence: 99%
“…Kim (2008) found that blogs are advantageous over traditional computer-mediated communication (CMC) applications in terms of their affordances of interactivity, openness, visualization, and decentralization. A vast multitude of other studies (e.g., Churchill, 2009;Glogoff, 2007;Halic, Lee, Paulus & Spence, 2010;Huck, 2007;Kang, Bonk, & Kim, 2011;Yang, 2009;Williams & Jacobs, 2004) have also acknowledged the educational advantages of integrating such a social media tool into the curriculum. For instance Makri and Kynigos (2007) investigated blogs applied in a graduate course.…”
Section: Introductionmentioning
confidence: 99%
“…The findings have been echoed by a number of other researchers. Williams and Jacobs (2004) also concluded that "blogs have the potential, at least, to be a truly transformational technology in that they provide students with a high level of autonomy while simultaneously providing opportunity for greater interaction with peers" (p. 145). The findings of Top's (2012) study "approved blogging as social media for learning about [learners themselves] and developing interactive connections with others" (p. 28).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of social networking tools, for example, blogs, encourage teachers, especially those in higher education, to break the boundaries of conventional practice logistics and pursue tele-collaborations with distant learner groups (e.g., Chen & Eslami, 2013;Williams & Jacobs, 2004). Facing the changes of instructional contexts and media, teacher intervention, specifically feedback, would evolve in response to new learning channels.…”
Section: Introductionmentioning
confidence: 99%